(untitled) (Forum Penelitian Agro Ekonomi, 2016)
This study analiyzes demand/consumption, supply/production, and marketing of horticulture (vegetables and fruits) related to its development in Indonesia. Descriptive analysis throught cross tabulation and trend analysis of production and consumption using seondary data from CBs and result, of several research on horticulture. The result of the analysis show that (1) consumption level of vegetable and fruits in 1992 is relatively low i.e 25.8 and 28.04 Kg/Capital/year respectively.This shows a high opportunity to develop horticultural production in Indonesia; (2)ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â in domestic market, the dominant factors influencing holticulture consumption are number of population (consumer) and growth of average population income (3) price fluctuation, improportional price transmission between producer-retailer, and perishable characteristic of the commodities are the main problems in horticulture marketing systemin Indonesia. To anticipate the opportunity of increasing demand both domestic and export markets, the efforts can be made are (1) intensification at the production centre areas, (2) extensification to create new production areas,ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â (3) special attention for developing specific tropical holticulture, andÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â (4) effeciency in marketing by improving transportation, packaging and storage systems